Biologia y enemigos nativos del picudo de los citricos Compsus n. sp. (Coleoptera: Curculionidae) - Cano L, D.M.=700 1 Bustillo P, A.E.; Cardenas M, R.; Orozco G, L.
(Es, En)
Ilus., 19 ref.
Keywords: CITRUS SINENSIS; INSECTA; COLEOPTERA; CURCULIONIDAE; ORGANISMOS INDIGENOS; BIOLOGIA; COLOMBIA; PICUDO DE LOS CITRICOS